IEEE 802.11 graph models - Jose Manuel Gimenez-Guzman; Ivan Marsa-Maestre; Luis Cruz-Piris; David Orden; Marino Tejedor-Romero (Alexandria Engineering Journal, 2023)
There are several recent research lines addressing Wi-Fi network planning and optimization, both in terms of channel assignment and access point deployment. The problem with these works is that evaluation is usually performed with specific and closed models regarding signal propagation, throughput computation, and utility definition. Also, many of the models in the literature make assumptions about the role of wireless stations, or the co-channel interference, which -while being valid in the context of a single research work- makes very difficult to compare different approaches, to re-use concepts from previous mechanisms to create new ones, or to generalize mechanisms to other scenarios. This makes the different research lines in Wi-Fi network planning and optimization progress in an isolated manner.This paper aims to address such a recurring problem by proposing a graph-based generic model for Wi-Fi utility computation in network planning scenarios, as well as providing a collection of scenario graphs which may be used to benchmark different planning and optimization approaches. Experiments are conducted to show the validity of the model and the significance of its features, along with its extensibility to other scenarios.